The dynamics of food for special medical purposes (FSMPs) utilization in cancer care: from doctor recommendations to online pharmacy procurement - Chereches, Marius Călin; Popa, Cristian Olimpiu; Finta, Hajnal (Frontiers in Pharmacology, 2024)
This cross-sectional study conducted in Romania examines the increasing role of online pharmacies in providing Food for Special Medical Purposes (FSMP) to cancer patients. Key findings indicate patient satisfaction with ease of access, significant challenges related to costs, and the critical role of healthcare professionals in guiding FSMP selection.Introduction. As cancer treatments advance, the demand for supportive nutritional care becomes increasingly critical, with FSMPs playing a vital role in patient recovery and quality of life.Methods. Employing a cross-sectional study design, we surveyed cancer patients from Romania to assess their experiences purchasing FSMPs through traditional and online pharmacies. We analyzed the factors influencing their choices, the perceived benefits and challenges of online access, and the role of healthcare professional guidance in their decision-making process.Results. The study reveals that while patients appreciate the ease of access and the broad spectrum of available FSMPs online, they grapple with the financial burden and the need for reliable information to make informed decisions. Through a cross-sectional analysis, we found that the expertise and recommendations of healthcare professionals remain integral to the FSMP selection process, suggesting that digital solutions should enhance, not replace, traditional healthcare interactions. Moreover, our findings highlight a crucial gap in the taste and variety of FSMPs, suggesting that patient adherence could be improved through product innovation. The study found a significant association between the type of medical unit where patients followed their treatment (state-owned clinic) and whether they received recommendations from a specialist oncologist for using FSMPs. Nutritionists' recommendations were also significantly associated with a higher likelihood of purchasing FSMPs online.Discussions. The study reveals that despite the benefits of digital access, a crucial need exists for regulatory measures and professional oversight to ensure the safe and informed use of FSMPs. The trust placed in healthcare professionals' recommendations continues to be instrumental in navigating the digital marketplace.Conclusions. This work paves the way for future strategies to integrate online solutions with established healthcare practices to optimize cancer care in the digital age.